A fully disposable paper-based electrophoresis microchip with integrated pencil-drawn electrodes for contactless conductivity detection. Issue 37 (25th August 2016) - Chagas, Cyro L. S.; de Souza, Fabrício R.; Cardoso, Thiago M. G.; Moreira, Roger C.; da Silva, José A. F.; de Jesus, Dosil P.; Coltro, Wendell K. T.
Abstract : We describe the development of a paper electrophoresis chip integrated with pencil electrodes for contactless conductivity detection and its application in the separation of biomolecules associated with kidney dysfunctions. Abstract : We describe for the first time the fabrication of a paper-based microchip electrophoresis (pME) device with integrated hand-drawn pencil electrodes to perform capacitively coupled contactless conductivity detection (C 4 D). This low-cost device (less than $0.10) revealed great capability to dissipate heat, good injection-to-injection repeatability, and ease of attaching pencil-drawn electrodes on the separation channel. The feasibility of the proposed pME-C 4 D device was successfully demonstrated with the separation of bovine serum albumin and creatinine within 150 s with baseline resolution. The limits of detection values for albumin and creatinine were 20 and 35 μmol L −1, respectively. These biomolecules present clinical relevance as evidence of kidney failure. The proposed pME-C 4 D offers great potential to be explored in the diagnosis of diabetes mellitus and heart disease.